Witness to Marvels - Stewart, Tony K. (University of California Press, 2019)
Witness to Marvels traces the development of a unique genre of Sufi-inspired Bengali romances called pir kathas, whose protagonists and plots are wholly fictive. For five centuries these fabulations have parodied indigenous and Hindu textual traditions. Both mimicking and mocking, these parodies adopted a subjunctive tone, exploring a magical world of 'what-if'. They created an Islam-inflected space within a traditional Bengali cultural environment without trying to legislate what ideally 'should be' according to tropes common to Islamic history, theology, and law. The tales' discursive arena, the imaginaire, delineated the realm of possibility for how these tales might exercise the imagination to integrate Hindu and Islamic cosmologies. Tales insinuated themselves into locally relevant discourses through elaborate intertextual connections, subtly shifting presuppositions about the way the world works and what counts as religious authority. As Allah looked on from heaven, the tales routinely assigned Sufi saints, both pirs and bibis, to the pivotal role of avatar, the periodic descent of divinity, equating them to the Hindu god Narayan. Adopting a semiotic strategy to interpret these tales yields a bold new perspective on the subtle ways Islam assumed its distinctive form in Bengal and suggests how we need to reimagine conversion in this region.